Public Infrastructure Investment, Interstate Spatial Spillovers, and Manufacturing Costs - Cohen, Jeffrey P.; Paul, Catherine J. Morrison (The Review of Economics and Statistics, 2004)
Effects of public infrastructure investment on the costs and productivity of private enterprises have proven difficult to quantify empirically. One piece of this puzzle that has received little attention is spatial spillovers. We apply a cost-function model to 1982–1996 state-level U.S. manufacturing data, to untangle the private cost-saving effects of inter- and intrastate public infrastructure investment. We implement two spatial adaptations—including a spatial spillover index in the theoretical model, and allowing for spatial autocorrelation in the stochastic structure. Recognizing such spillovers both increases the estimated magnitude and significance of cost savings from intrastate public infrastructure, and augments these productive effects.